FEATURES OF CHILD-PARENTS FAMILY RELATIONSHIP WHO ARE INVOLVED IN FAMILY BUSINESS - Markova, Anna (PSYCHOLOGICAL JOURNAL, 2016)
The purpose of the work – to conduct a comparative analysis of traits of the attitude of children to parents and family, as well as traits of attitude of parents to children in families who are running family businesses in order to confirm the hypothesis about the deformation of the family system of child-parent relationship if the involvement of the second generation of owners to work in a joint business forced, and to identify possible targets of correction. Contingent and methods of research – during 2014-2016 years on the basis of medical and psychological center “Aiva” (Kyiv city) with the principles of bioethics and ethics were examined in complex 85 family members who were running family businesses. Design of investigation included participation of two generations: parents – business founders and their adult children who were involved in business. The group of business founders included men of 43 to 59 age, average age 51±3,1 years old. The group of the second generation of business founders (children) involved young men from 23 to 29 age, average age 25,5±1,7 years old. The survey included the use of socio-demographic, clinical and psychological and psychodiagnostic methods, the results of which were subjected to the processing methods of mathematical statistics. The results. Among the total number of motives that determined the participation of children in the parent business, we identified three major (p <0.01), described by the identified trends: a) submission to their fathers’ wish with hidden inside resistance – group 1 – 32 families (37,6%); b) passive agree and adaptation – group 2 – 21 families (24,7%); c) sincere desire of younger generation – group 3 – 32 families (37,6%). Results of research show significant differences in the state of child-parent interactions in families involved in joint business, depending on the motivation of participation of the second generation of owners. Families where adult children took part in the family business by their own wish, was a positive, constructive type of child-parent interaction, expressed a positive attitude of children to parents and family as well as constructive attitude of parents to adult children. In families in which adult children took part in the family business by passive agree and adaptation was an indifferently-deforming type of parent-child interaction, which is characterized by nudged aside indifferent attitude of children to parents and deforming-negative attitude to them by parents. In families in which adult children took part in the family business by force, with submission to their fathers’ wish, was a negative, destructive type of child-parent interactions in which the negative attitude of children to fathers and paternal family was congruent destructive towards parents to children. Conclusion. The data we received was taken into account while the development the system of psychological correction measures and psychological support of family members who are involved in family business.